Students' experiences in guided computer-based learning: A progressive evaluation - Katuk, Norliza (IEEE Explore, 2012)
This study investigated students’ experiences in two types of instructional strategies (i.e., fully-guided and partially guided) and their learning experience patterns from the beginning towards the end of the computer-based interactions. An empirical study was performed on 41 students from a public university in Malaysia using two types of computer-based systems for learning Basic Computer Networks. The students’ learning experiences were evaluated at three different stages of the computer-based learning sessions using self-report technique. The results showed that the students’ learning experiences were changing over the period of the computer-based lessons either in positive or negative ways. The directions of changes were mainly influenced by the students’ Information Technology (IT) prior knowledge. The results of this study suggest that computer-based guided learning systems should consider students’ background of knowledge in their design to achieve effective learning. Further,the combination of the fully-and partially-guided features may create an adaptive computer-based learning system.